Impact of corporate governance characteristics on earnings management - Paiva, I. (World Finance Conference, 2020)
The main objective of this study is to analyse the impact of corporate governance characteristics on the levels of earnings management, with reference to British companies listed on the London Stock Exchange between 2014 and 2017. A linear regression model was used, based on discretionary accruals, calculated using Kothari et al. (2005) and corporate governance features. The main results show that the greater the long-term remuneration of the board members, the higher the level of earnings management and the greater the presence of women on this board, the greater the proportion of non-executive members in the audit committee and so the greater the fees paid to external auditors. The findings presented in this study contribute to a better understanding of the relationship between corporate governance and earnings management in UK listed companies.